(untitled) (Annual of the Faculty of Philosophy in Skopje, 2018)
This paper explains the delicate relationship between the media and terrorism in order to achieve a better understanding of the relationship between the two entities. In this paper, we will study both how publicity benefits terrorists, and how the media benefits from the acts of terrorists. The present paper will attempt to answer the following questions: How can we rethink the sensationalist coverage of terrorism and stop providing terrorists a free media platform? What kinds of relationships exist between terrorist groups and the media? To what degree can the media itself be held responsible for providing terrorism with the “oxygen of publicity”? Is it possible for the media to objectively report about terrorists without promoting their actions and instigating fear? The purpose of this paper will be focused on the relationship between media coverage and terror attacks themselves, raising the question of whether increased coverage has an effect on the increased number of terrorist attacks.